Discourse Network Analysis on News of Fuel Price Increases in the Susilo Bambang Yudhoyono Government in 2013 and the Joko Widodo in 2022 - Nezar Patria; Budi Irawanto; Ana Nadhya Abrar (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The subsidized fuel price increase poses a significant policy challenge in Indonesia, characterized by complexities in decision-making and implementation. This study investigates the mediatization of political discourse surrounding this issue during two distinct periods: 2013, under President Susilo Bambang Yudhoyono (SBY), and 2022, under President Joko Widodo (Jokowi). Employing the Discourse Coalition Framework (DCF) and Discourse Network Analysis (DNA), the research analyzes media narratives on fuel price increases published by Detik.com, one of Indonesia's most prominent digital media outlets. The findings reveal a notable shift in discourse coalitions between the two periods. In 2013, opposition to the policy was primarily voiced by politically affiliated actors, whereas in 2022, civil society figures emerged as the dominant counteractors. Supportive narratives, however, consistently stemmed from government-aligned individuals in both periods. By comparing the actors involved, the arguments presented, and the evolution of discourse over time, this study highlights the changing dynamics of mediatized policy debates. Moreover, Detik.com demonstrated a balanced mediatization of supportive and opposing perspectives, with government-affiliated voices predominating in support, and opposition transitioning from political elites in 2013 to civil society in 2022. These findings underscore the media's evolving role in fostering issue-focused narratives, reducing polarization, and facilitating informed public discourse on contentious policy issues.